Evaluasi Dampak ASI Non-Eksklusif dan Gaya Pengasuhan Nutrisi terhadap Risiko Stunting Anak di Komunitas Nelayan Medan Labuhan - Widyastuti Widyastuti; Herny Misnita; Yulinda Aswan (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Stunting is a serious public health issue in Indonesia, with long-term impacts on children’s physical and cognitive development. Fishing communities often face challenges in accessing adequate nutritional information and resources, making it crucial to examine the contributing factors to stunting in these environments. The high prevalence of stunting in coastal areas of Medan, including Medan Labuhan, underscores the urgency of this study. Factors such as low parental education, limited nutritional knowledge, and poor economic conditions contribute significantly to the high incidence of stunting. In addition, non-exclusive breastfeeding practices and suboptimal nutritional parenting styles serve as major risk factors affecting child growth. This study aims to evaluate the impact of non-exclusive breastfeeding and nutritional parenting styles on the risk of stunting among children under five in the fishing community of Medan Labuhan. A quantitative approach with a cross-sectional design was employed, involving 100 respondents selected purposively from Kampung Nelayan Indah, Medan Labuhan. Data were collected through structured questionnaires and anthropometric measurements of children aged 24–59 months. The data were analyzed using chi-square and logistic regression tests. The results indicated that most variables—such as exclusive breastfeeding, breastfeeding frequency, age of complementary feeding introduction, caregiver, number of food types, and daily meal frequency—were not significantly associated with children’s nutritional status (p > 0.05). However, food refusal behavior (≥ 3 times/day) showed a significant association (p < 0.05), indicating that children who frequently refused food were more likely to experience poor nutritional status.